DUAL PROMOTION OF Cu/ZnO CATALYSTS MODIFIED BY ACETYLACETONE PRECURSORS FOR CO2 HYDROGENATION TO METHANOL - Junjie Xian; Yuntian Xua; Gaocheng Qu; Wei Na; Hua Wang; Wengui Gao (Química Nova, 2024)
It is challenging to reveal the catalytic mechanism of Cu/ZnO catalysts with multivalent copper and improve the performance of CO2 hydrogenation to methanol. We synthesized Cu/ZnO catalysts with different Cu:Zn ratios using acetylacetone salts as the precursors, in which Cu, Cu2O, CuO coexist. The catalytic activity was significantly associated with the abundance of Cu+ active sites on the surface and the formation of more Cu+-ZnO interfaces. When the ratio of Cu:Zn = 5:4, the catalyst without reduction pretreatment showed good performance, with a CO2 conversion rate of 12.9%, methanol selectivity of 85.1%, and the space-time yield of 0.238 gMeOH gcat−1 h−1. It was suggested that Cu+ tends to closely bind with ZnO, and the preparation method leads to more Cu+-ZnO interfaces. The synergistic interaction between Cu+ and ZnO promoted the adsorption and dissociation of CO2 and H2, verifying its dual effect on CO2 and H2 and promoting CO2 hydrogenation to methanol.